The effect of carboxylate position on the structure of a metal organic framework derived from cyclotriveratrylene - Martin, Adam D.; Easun, Timothy L.; Argent, Stephen P.; Lewis, William; Blake, Alexander J.; Schröder, Martin (Royal Society of Chemistry, 2016)
Two cyclotriveratrylene-based ligands H3L1 and H3L2 have been synthesised using microwave heating and used in the formation of 1 [Zn2(L1)(DMA)2(CH3COO)] and 2 [Zn6(L2)4(DMA)6(H2O)5] (DMA = N,N-dimethylacetamide). 1 displays an unusual trigonal paddlewheel node geometry, while Zn(II) paddlewheels are observed in 2. However the stacking of CTV molecules in 1 is replaced by an uncommon molecular capsule structure in 2.